Biaxial creep of high-strength concrete at early ages assessed from restrained ring test. (November 2019) - Liang, Siming; Wei, Ya
Abstract: High-strength concrete structures are prone to cracking due to the large tensile stress induced by the restrained deformation. Creep can efficiently relax such stress, thus reducing the crack risk. Concrete structures may be subjected to multiaxial stress when the shrinkage deformation is restrained, however, the multiaxial creep property of early-age concrete is still far from clear. This study employed restrained ring test to investigate the basic creep property of high-strength concrete under biaxial tensile-compressive stress condition at early ages. A finite element analysis based-method was proposed to retrieve the biaxial creep of concrete based on the measured strain of the steel ring. The uniaxial tensile and compressive creep properties of high-strength concrete were also measured at different ages including 1, 7, and 28 days, which were compared with that obtained from the restrained ring test. The results show that concrete creep under both uniaxial and biaxial stress conditions decreases with increasing loading age. However, the creep under the biaxial tensile-compressive stress condition is only about 54–63% (41–75%) of that under the uniaxial tensile (compressive) stress condition, suggesting that stress condition is a key factor that affects the creep property of high-strength concrete at early ages. The findings in this study can provide new insight into the creep effect on the restrained stress calculation and crack risk assessment of the high-strength concrete structures.